Chronic Exercise Promotes Alterations in the Neuroendocrine Profile of Elderly People - Alves, E. S.; Souza, H. S.; Rosa, J.P. P.; Lira, F. S.; Pimentel, G. D.; Santos, R.V. T.; Oyama, L. M.; Damaso, A. R.; Oller do Nascimento, C. M.; Viana, V.A. R.; Boscolo, R. A.; Grassmann, V.; Santana, M. G.; Tufik, S.; de Mello, M. T. (Hormone and Metabolic Research, 2012)
Aging and physical inactivity are 2 factors that favour the development of cardiovascular disease, metabolic syndrome, obesity, and diabetes. In contrast, adopting a habitual moderate exercise routine may be a nonpharmacological treatment alternative for neuroendocrine aging disorders. We aimed to assess the effects of moderate exercise training on the metabolic profiles of elderly people with sedentary lifestyles. Fourteen sedentary, healthy, elderly male volunteers participated in a moderate training regimen for 60 min/day, 3 days/week for 24 weeks at a work rate equivalent to their ventilatory aerobic threshold. The environment was maintained at a temperature of 23±2°C, with a humidity of 60±5%. Blood samples for analysis were collected at 3 intervals: at baseline (1 week before training began), and 3 and 6 months after training. The training promoted increased aerobic capacity (relative VO2, and time and velocity to VO2max; (p<0.05)) and reduced serum α-MSH (p<0.05) after 3 months of training when compared with the baseline data. In addition, serum thyroid hormone (T3 and T4) was reduced after 6 months of training compared with baseline levels. Our results demonstrate that a moderate exercise training protocol improves the metabolic profile of older people, and metabolic adaptation is dependent on time.
Keywords: aerobic capacity; neuropeptides; aging; moderate training